Bank Information Disclosure, Financial Transparency and Corporate Governance in Rastin Banking - Bidabad, Bijan; Sherafati, Mahshid (International Journal of Shari'ah and Corporate Governance Research, 2019)
Purpose: This paper aims to define a set of banking operating regulations for financial transparency, corporate governance, and bank information disclosure.Design: Bank governance, financial transparency, and information disclosure are amongst the most important solutions to attract public trust to financial and banking operations. In order to reach this goal, a new set of regulations should be designed to solve the problem. In this way, Rastin Banking regulations can provide a base to obtain a better information circulation and higher clarity.Findings: A draft of regulations for financial transparency, governance, and bank information disclosure is presented in this paper, which can be employed as a basis for the codification of the respective law.Research limitations: Since such kinds of regulations are novel for banks, they are required to be meticulously scrutinized in the first place, and after adaptation, adjustment, and performing the necessary modifications, the code of law can be codified.Practical implications: Bank managers, through granting various concessions to themselves and their own stakeholders, have violated the rights of shareholders, depositors, and other stakeholders. This issue, through applying the governance methods, is adjustable to a great extent.Social implications: This procedure is a model that can be adopted in other countries, especially those countries that have essential ambiguities in their banking and financial operations.Value: Clearly, the lack of transparency in banking operations can gradually weaken the trust of depositors, stakeholders, and shareholders, and result in probable abuses and damages to all parties in the bank’s contracts. This article fulfills an identified need and solves the practical problem in financial abuses, corruption, and collusion, and can provide positive and essential effects on creating public trust in financial operations.